Extensive Intra Abdominal Hydatid Cysts (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Human hydatid cyst is an illness caused by the cystic phase of the small trepanoma, Echinococcus granulosus. It is an endemic disease in some countries of the world. Hydatid disease though known to occur in almost all organs of the body, it is extremely rare in the female reproductive organs. In this report we present a case of hydatid disease of both ovaries with widespread intraabdominal hydatid cysts. This case was misdiagnosed as an ovarian cyst until the time of operation. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20983 J Bangladesh Coll Phys Surg 2013; 31: 156-158